(untitled) (REVISTA SAYWA, 2020)
Propolis is a natural product collected and processed by bees that consists of a resinous mixture of chemical composition changing from region to region in the world. The antitumor effect of propolis from different geographical areas has been widely reported. In this work, we made a chemical characterization of four ethanol extracts of Colombian Propolis (EEP) and their cytotoxic action against canine osteosarcoma cells (OS) and fibroblasts derived from a primary canine culture was evaluated. In addition,changes in the gene expression of apoptotic, associated with inflammation and the cell cycle, were evaluated in these two cell types. The results indicate an antiproliferative activity of propolis on OSCA-8 tumor cell line, highlighting a greater cytotoxic effect in these cells with respect to fibroblasts. Furthermore, an increased in the expression of proinflammatory and proapoptotic genes and proapoptotic processes were found in cells treated with EPP.